Pengaruh Shopping Lifestyle dan Positive Emotion Terhadap Impulse Buying (Studi Pada Konsumen UD Putra Tiga Saudara Majalengka) (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2020)
This purpose of this research is to find out the influence of a shopping lifestyle and positiveemotion against impulse buying on UD Putra Tiga Saudara Majalengka consumer, buyingeither partially or simultaneously. This research is a survey research using descriptive andverification approaches. The sample of this research is 150 people. They are concumer of UDPutra Tiga Saudara Majalengka. Data collectionof this research used questionnaire method.Likert measurement scale is used on this research. The analysis of data processing is usedSPSS 21. Data analysis were performed using test of validity, reliability, the test of the classic,coefficient determination analysis and hypothesis testing using t test and F test. The resultsobtained of shopping lifestyle, positive emotion, and with impulse buying in UD Putra TigaSaudara Majalengka including high category. As for influence of shopping lifestyle andpositive emoton of impulse buying partially and simultaneously have a positive and significanteffect.